Effect of Mangifera indica L. on hyperglycemia, hyperlipidemia and atherogenicity in diabetic mice - Ai Lan, Nguyen Thi; Xuan Trang, Dai Thi (Academia Journal of Biology, 2018)
In this study, the antihyperglycemic and antihyperlipidemic effects of Mangifera indica L. (MIL) young leaves extract were investigated using diabetic mice models. Male Mus musculus L. mice were intratoripeneally injected by Alloxan monohydrate (AM) to induce diabetes and were observed for 28 days. The blood glucose, total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL_C), low-density lipoprotein cholesterol (LDL_C) and atherogenic index were evaluated. The acute toxicity of MIL was determined at the dose of 1000, 2500, 5000 mg/kg body weight of normal mice. Diabetic mice were orally administrated with extract of MIL (150, 300, 450 mg/kg body weight/ twice a day). The results showed that the MIL significantly decreased the plasma glucose, TC, TG, LDL_C levels and atherogenic index and greatly elevated the HDL_C level in diabetic mice (p<0,05). The methanol extract of young leaves showed the antidiabetic and antihyperlipidemic potential. Altogether, Mangiferine indica L. leaves could be considering as a promising therapy in preventing the complications of diabetes